PENGARUH MANAJEMEN LABA, CSR, LIKUIDITAS, DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK - Jasman Jasman; Mega Dwi Mustika (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this study is to analyze the effect of liquidity, leverage, Corporate Social Responsibility (CSR), and earnings management towards tax aggressiveness. The object of this study is state-owned enterprise for the period of 2016-2020. The sampling technique used is a purposive sampling method. The analytical method uses in this study is multiple linear regression. The results show that liquidity has a negative and significant effect on tax aggressiveness. Corporate Social Responsibility has a positive and significant effect on tax aggressiveness. Meanwhile, leverage and earnings management have no effect on tax aggressiveness. These results suggest that state-onwed enterprise should maintain their liquidity to minimaze tax aggressiveness practices